KAJIAN TEORI: MODEL PEMBELAJARAN QUANTUM TEACHING BERBANTUAN APLIKASI CONSTRUCT 2 MATERI BANGUN RUANG SISI DATAR UNTUK MENINGKATKAN PEMAHAMAN MATEMATIS SISWA - Dhaka Prabowo, Akbar (LPPM STIT Muhammadiyah Tempurejo Ngawi, 2023)
Comprehension ability is an initial ability that students must master before proceeding to a deeper discussion of the material, because this comprehension ability is the lowest level in cognitive aspects and is one of the important goals in learning, because it gives an understanding that the materials taught to students are not only memorized, but more than that. A teacher has an important role in terms of improving students' mathematical abilities, namely by applying innovative learning models. However, in reality there are still many teachers who use a learning model that is less attractive, which can cause students to feel bored and the learning process becomes ineffective and inefficient. To overcome this, a quantum teaching learning model can be applied. Quantum Teaching is an interaction that converts energy into light. The subject matter in quantum teaching relates to the student's experience in general so that learning is not abstract anymore. This is the point of causing quantum teaching to become an effective and efficient learning model. Thus, the application of quantum teaching can be one of the alternative teachers in the learning process. Students' mathematical understanding can also be improved by the existence of supporting learning media, namely the use of the construct 2 application by teachers. The writing of this article aims to find out how quantum teaching learning models assisted by construct 2 applications can improve students' mathematical understanding of flat-sided space building materials. The results of the discussion showed that the quantum teaching learning model assisted by the construct 2 application can improve students' mathematical understanding of flat-sided space building materials.